Keamanan Jaringan Wireless Dengan Kali Linux - Rasyidah; Fajar Setyawan; Hidra Amnur (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2022)
The development of wireless technology or wireless produces something interesting to discuss. Wireless technology is not always about how fast communication can be done. Security issues are very important to discuss, especially in an era that is all digital and all minimalist which no longer requires cables. Security needs to be considered to provide a sense of security when using a device connected to a Wi-Fi. For that, it is necessary to do a security analysis on a wifi. This analysis is carried out using the Penetration Testing method by carrying out attacks to find weaknesss in the Wi-Fi network security system. So, you will see the strength of the password on the Wi-Fi network. Security testing is also carried out on the communication path between clients and access points. So that from the results of this test it will be seen how safe the Wi-Fi network security system is